KAJIAN KONSENTRASI EKSTRAK BAWANG MERAH DAN LAMA PERENDAMAN TERHADAP PERTUMBUHAN STEK LADA (Piper nigrum L.) - Sulastri, Yustina Sri; Gusriani, Yunda; Barasa, Jojong Sah Kian; Rajagukguk, Fransisco (Agroprimatech, 2023)
This research aims to determine the effect of shallot extract concentration and soaking time on the growth of pepper plant stems. This research was carried out at the Unika Santo Thomas Medan agricultural experimental field Jl. Setia Budi no. 479, Tanjung Sari, Medan. With a height of around 32 meters above sea level (meters above sea level). This research was conducted from March to May 2023. This research used a factorial Randomized Block Design (RAK) consisting of 2 factors. The first factor is the concentration of shallot extract (K) and the second factor is the soaking time (P). The first factor is the concentration of shallot extract (K) consisting of 4 treatment levels, namely: K0: 0% (control), K1: 30% (30 mL of shallot extract + 70 mL of distilled water), K2: 60% (60 mL of shallot extract + 40 mL distilled water), K3: 90% (90 mL shallot extract + 10 mL distilled water). The second factor is the length of soaking of pepper plant cuttings (P) consisting of 3 treatment levels, namely: P1: 3 hours, P2: 6 hours, P3: 9 hours. Based on the research results, it can be seen that the concentration of onion extract has no effect on the percentage of live cuttings of pepper plant cuttings, but it has a real influence on the length of the shoots with the highest shoots obtained at a concentration of 93.33% at a concentration of 83.77% for the number of leaves. the most. Regarding the number of roots, a concentration of 78.66% produced the highest number of roots.